ULTRON : managing warehouse space and item obsolescence - Roy, Debjit; Pratap, Mayank; Raj, Premm H. (London : Indian Institute of Management, Ahmedabad, 2018)
The case focuses on the ULTRON's logistics problems in its warehouse in 2016. The warehouse contained a growing portfolio of products that were older than 180 days. The main reason for the dated inventory was the absence of a warehouse management system, which resulted in a failure to implement First-in First-out (FIFO) sequence of the products in the warehouse. Given the substantial investment costs associated with installing a new warehouse management system, warehouse manager Ahuja must evaluate other alternatives for implementing FIFO at his manually operated warehouse.
Originally Published InRoy, D., Pratap, M., & Raj, P. H. (2018). ULTRON: Managing Warehouse Space and Item Obsolescence. PROD0317. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; ULTRON -- Case studies; Warehouses -- Management -- Case studies